Kebijakan Pengelolaan Sumber Daya Alam dalam Perspektif Good Governance - Taufik Hidayat (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
God lavishes Indonesia with natural resources are very abundant, so we are proud to say "what the hell do not we have?". On the other hand, there are still many residents of this country are still far below the poverty line. Naturally, the question arises advanced "what's wrong?". The research method used is qualitative method used descriptive exploratory approach. Approach descriptive exploratory study conducted by the document. Based literature review concluded that there had been "mismanagement" in the management of natural resources (as above), should any sda management policy rests on the principles of good governance which is the organizing principle of good State: 1) Participation, 2)Rule of law, 3) Transparancy, 4) Responsive, 5) Consensus Orientation, 6) Equity, 7) Effectiveness and efficiency, 8) Accountability, 9) Strategic vision.